GAMBARAN STATUS GIZI PEKERJA BANGUNAN WANITA DI KECAMATAN TEMBALANG KOTA SEMARANG TAHUN 2016 - Danan Surya Fitriananto; Laksmi Widajanti; Ronny Aruben; M. Zen Rahfiluddin (Jurnal Kesehatan Masyarakat (Undip), 2018)
On-site construction work for women is heavy, and the complexity of the factors is direct. Nutrition status in workers has an important role, both for the interest and in order to improve discipline and work productivity. Therefore, it is needed and in accordance with the type or work performed. This research is an observational analytic research with cross-sectional approach. Data were collected using questionnaires and body mass index instruments (IMT). The research was conducted in four housing in Tembalang sub-district, Bukit Cemara Residence, GriyaTembalang Sejahtera, Citra Grand, and Bukit Pandanaran. The number of samples in this study using Lamesshow sample formula is 67 women workers. Female construction workers who have thin category have 3 people (4.9%) who have high productivity level and 3 people (4.9%) who have low porductivity level. Women with normal nutritional status are 25 people (40.9%) who have high productivity and 7 people (11,4%) have low level. Meanwhile, on nutritional status of fat there are 8 people (13,1%) which have high productivity and 15 people (24,6%) have low level. There is correlation of nutrient status with work productivity at woman worker of building in Tembalang Sub-district Semarang City.